Contagion as a Dealmaker? : The Effect of Financial Spillovers on Regional Lending Programs - Fotiou, Alexandra (IMF Working Papers; Working Paper ;, 2022)
The recent European sovereign debt crisis highlighted the critical role of regional lending arrangements. For the first time, European mechanisms were called to design financing programmes for member countries in trouble. This paper analyses how the risk of contagion, an essential characteristic of interlinked economies, shapes borrowing conditions. We focus on the role of spillovers as a channel of bargaining power that a country might have when asking for financial support from regional lending institutions. We build and present a new database that records both the dates on which official meetings took place, relevant statements were released and the timing of the announcements regarding loan disbursements. This database allows us to assess the defining role that announcements of future actions have in mitigating spillover costs. In addition, we study the design of lending arrangements within a recursive contract between a lender and a sovereign country. When accounting for spillover costs, arising from the borrower to the creditor, we find that it is in the lender's best interest to back-load consumption by giving more weight to future transfers in order to reduce contagion cost. Subsequently, we test and validate our theoretical predictions by assessing the effect of spillovers on loan disbursements to programme-countries and by juxtaposing lending conditions imposed by the IMF and the European mechanisms.